2021
DOI: 10.1002/lrh2.10259
|View full text |Cite
|
Sign up to set email alerts
|

Creating learning health systems and the emerging role of biomedical informatics

Abstract: Introduction:The nature of information used in medicine has changed. In the past, we were limited to routine clinical data and published clinical trials. Today, we deal with massive, multiple data streams and easy access to new tests, ideas, and capabilities to process them. Whereas in the past getting information for decision-making was a challenge, now, it is how to analyze, evaluate and prioritize all that is readily available through the multitude of data-collecting devices. Clinicians must become adept wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Kohn et al recently suggested that the approach to informatics training constitutes in and of itself a learning health system. 6 They posited three distinct elements of the institutional biomedical informatics LHS:…”
Section: Resultsmentioning
confidence: 99%
“…Kohn et al recently suggested that the approach to informatics training constitutes in and of itself a learning health system. 6 They posited three distinct elements of the institutional biomedical informatics LHS:…”
Section: Resultsmentioning
confidence: 99%
“…Although major challenges related to data governance/ management, 135,[175][176][177][178][179][180][181][182][183] ethical/legal, [184][185][186][187] and environmental 188,189 considerations would need to be addressed, these "dynamic multimodal ML models" may become cost-effective in different populations 169,[190][191][192][193] if conceived as the integrative tools needed to provide precision health 22,164,165,168,[194][195][196] and support some of the iterative cycles of knowledge generation and continuous improvement of "learning health systems". 11,[197][198][199][200]…”
Section: Opportunitiesmentioning
confidence: 99%
“…8,13 As frontline clinicians working in both ambulatory and inpatient settings across multiple teams, housestaff have first-hand knowledge of complex and varied workflows and have a vested interest in identifying, implementing, and improving patient care and system usability. 8,[14][15][16] Despite these opportunities, housestaff are an underutilized resource, often relegated to being recipients of system changes, rather than primary drivers and champions.…”
Section: Background and Significancementioning
confidence: 99%